2003
DOI: 10.1103/physreve.67.056402
|View full text |Cite
|
Sign up to set email alerts
|

Weakly dissipative dust-ion-acoustic solitons

Abstract: We investigate the possibility for dust ion-acoustic solitons to exist. Compressive solitonlike perturbations are damped and slowed down, mainly due to the plasma absorption and ion scattering on microparticles. The perturbations are shown to possess the main properties of solitons. There is a principal possibility to study experimentally the role of trapped electrons in the soliton formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(69 citation statements)
references
References 15 publications
4
65
0
Order By: Relevance
“…The velocity of the nonlinear dust ion-acoustic wave therewith depends strongly on the amplitude of the wave. Such a conclusion is confirmed, in particular, by the results of the investigation of the dust ion-acoustic solitons [9], where it was shown that the form of the evolving compressive soliton (damped and slowing down due to the interaction with dust) is given by the "conservative" soliton solution for the corresponding Mach number at any moment. This can be explained only if the velocity of the evolving dust ion-acoustic soliton depends mainly on its amplitude.…”
Section: Interpretation Of Experimentsmentioning
confidence: 61%
See 1 more Smart Citation
“…The velocity of the nonlinear dust ion-acoustic wave therewith depends strongly on the amplitude of the wave. Such a conclusion is confirmed, in particular, by the results of the investigation of the dust ion-acoustic solitons [9], where it was shown that the form of the evolving compressive soliton (damped and slowing down due to the interaction with dust) is given by the "conservative" soliton solution for the corresponding Mach number at any moment. This can be explained only if the velocity of the evolving dust ion-acoustic soliton depends mainly on its amplitude.…”
Section: Interpretation Of Experimentsmentioning
confidence: 61%
“…However, in contrast to classical collisionless shock waves, the dissipation due to dust charging involves interaction of electrons and ions with dust grains through microscopic electron and ion currents to the grain surfaces. The anomalous dissipation plays a very important role in the propagation of other dust ion-acoustic nonlinear structures, e.g., in the case of the so-called "weakly dissipative" dust ion-acoustic solitons [9], whose shape is described by soliton solutions in a certain range of values of the Mach number. Because of the anomalous dissipation, these solitons are slowed down and damped.…”
Section: Introductionmentioning
confidence: 99%
“…Later, these waves have been observed in laboratory experiments (Nakamura et al 1999). Extensive work has been devoted to the study of DIA solitary waves in dusty plasmas which have wide applications to various physical situations in space and laboratory plasma (Kourakis and Shukla 2004;Bharuthram and Shukla 1992;Popel and Yu 1995;Alinejad 2010Alinejad , 2011El-Labany et al 2008;Vladimirov 1997;Pakzad 2010;Shukla and Mamun 2003;Popel et al 2003;El-Labany et al 2003;.…”
mentioning
confidence: 98%
“…These opposite polarity ions and opposite polarity dusts [10][11][12][13][14] can significantly modify the basic properties of linear and nonlinear DIA SWs and DA SWs. The anomalous dissipation in complex plasmas, which originates from the dust charging process, makes possible the existence of a new kind of shock wave [21][22][23][24][25]. When the dissipation is weak or absent at the characteristic dynamical time scales of the system, the balance between nonlinearity and dissipation is weak at the characteristic dynamical time scales of the system, the balance between nonlinearity and dissipation effects can result in the formation of a symmetrical SWs.…”
Section: Introductionmentioning
confidence: 99%